Antibody response and protection of inactivated-local isolate vaccine for infectious bronchitis in laying chicken - Indriani, Risa; ., Darminto (Indonesian Animal Sciences Society, 2001)
Infectious bronchitis (IB) is an acute highly contagious viral respiratory disease of poultry caused by Coronavirus. IBV infection consists of many serotypes and can only be controlled by vaccination. An effective IB vaccine should be prepared from local isolates, due to the antigenic variation among serotypes. The aims of this research were to develop inactivated IB vaccine derived from IBV local isolate and to determine the efficacy of that vaccine in layer flocks. Five layer chicken groups were used in this experiments, group I was vaccinated with commercial IBV live vaccine thrice, group II was vaccinated with commercial IBV live vaccine once and repeated with inactivated local IBV isolate twice, group III was vaccinated with commercial IBV live vaccine once and repeated with commercial inactivated twice, group IV was vaccinated with IBV live vaccine once, and group V was not vaccinated. After the chickens reached at a stable egg production they were challenged with IBV local isolates. Antibody responses were examined by means of haemagglutination hibitition (HI) test and HI titres were expressed as log2 of the reciprocal of the highest dilution of serum causing inhibition of a log2 HA titre of 2. The mean titres of antibody responses of chicken in group I, II, III, IV, and V was 4.9 ± 0.87, 6.8 ± 0.97, 7.7 ± 0.46, 2.9 ± 0.94, and 2.0 ± 1.67 respectively. The levels of protection against challenges were determined by viral isolation, this in group I, II, III, IV, and V was 63, 73, 60, 50, and 0% respectively. Clinical symptom of egg quality was slightly reduced in group I, IV, and V and it were unchanged in group II and III. Group II gave better in number of egg production than the other groups. The results indicated that the IBV inactivated localisolate vaccine gave high titres of antibody and higher protection rates than that of commercial IBV inactivated vaccine. Inaddition, IBV local isolate vaccinated group prevented from declining egg production after challenged with IBV local isolate. Key words: Infectious bronchitis, layer, antibody titre, vaccine, challenge virus